Histopathological prognostic factor comparison of endometrial cancer patients in a tertiary hospital in India - Latha, P. Swarna; Chaitanya, Balekuduru; Reddy, S. Rajasekhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective of this study was to describe the histopathological features of patients with endometrial cancer in a tertiary hospital in South India. Methods: This retrospective study included cases diagnosed and operated in a tertiary hospital in the period of 3 years. Histopathological data was retrieved from records and analyzed. The study included both endometrial biopsy and post hysterectomy specimens of which prognostic factor comparison was performed on the latter following TNM and FIGO staging systems. Results: The sample consisted of 43 patients which includes 28 resected and 15 biopsy specimens. Age ranged from a minimum of 27 years to a maximum of 75 years (Mean around 52 years). Endometrioid adenocarcinoma was the predominant histological subtype (80 – 85%), while other types included papillary serous adenocarcinoma, stromal sarcoma and malignant mixed mullerian tumour (MMMST). Grade I tumours were 19 in number constituting 79.16% and stage IB tumours were the commonest. Pelvic nodal involvement, lymphatic invasion and recurrence were individually noted in one patient each. Conclusions: This study highlights the prognostic characteristics of endometrial cancer patients with most of them presenting in early stages thereby having a good prognostic outcome.